Impact of inhaled nitric oxide therapy in patients with cardiogenic shock treated with veno-arterial extracorporeal membrane oxygenation combined with Impella: a retrospective cohort study - Nobuhiro Yamada; Masafumi Ueno; Kyohei Onishi; Keishiro Sugimoto; Kazuyoshi Kakehi; Kosuke Fujita; Koichiro Matsumura; Gaku Nakazawa (Journal of Intensive Care)
Abstract Background The mortality rate of patients with cardiogenic shock (CS) requiring veno-arterial extracorporeal membrane oxygenation (VA-ECMO) combined with Impella (ECPELLA) support remains high. Inhaled nitric oxide (iNO) improves right ventricular (RV) function, resulting in increased Impella flow, which may facilitate early withdrawal of VA-ECMO and improve survival. This study investigated the prognostic impact of iNO therapy in ECPELLA patients. Methods We retrospectively analyzed the data of consecutive patients with CS supported by ECPELLA from September 2019 to March 2024 at our hospital. Changes in pulmonary artery pulsatility index (PAPi) and Impella flow over time were evaluated, and VA-ECMO withdrawal rate, time to withdrawal, and 30-day survival were compared between ECPELLA patients with and without iNO therapy. Results Of the 48 ECPELLA patients, 25 were treated with iNO. There were no significant differences between the groups in baseline characteristics or lactate levels at mechanical circulatory support induction. Patients with iNO therapy demonstrated significant improvements in the PAPi over time and a trend toward increased Impella flow, as well as a significantly higher VA-ECMO withdrawal rate (88% vs. 48%, P = 0.002) and a shorter time to VA-ECMO withdrawal (5 [3–6] days vs. 7 [6–13] days, P = 0.0008) than those without iNO therapy. Kaplan–Meier analysis demonstrated that the 30-day survival rate was significantly higher in patients with iNO than in those without (76% vs. 26%, P = 0.0002). Conclusions iNO therapy in patients with CS requiring ECPELLA was associated with short-term prognosis by improving RV function and facilitating weaning from VA-ECMO. Trial registration Retrospectively registered in UMIN-CTR (Reference No. R00006352).